2016
DOI: 10.1111/bjh.14061
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and patient survival of myeloproliferative neoplasms and myelodysplastic/myeloproliferative neoplasms in the United States, 2001–12

Abstract: Summary Descriptive epidemiological information on myeloproliferative neoplasms (MPNs) and myelodysplastic (MDS)/MPNs is largely derived from single institution and European population-based studies. Data obtained following adoption of the World Health Organization classification of haematopoietic neoplasms and JAK2 V617F mutation testing are sparse. Using population-based data, we comprehensively assessed subtype-specific MPN and MDS/MPN incidence rates (IRs), IR ratios (IRRs) and relative survival (RS) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 59 publications
4
121
1
9
Order By: Relevance
“…The majority of studies included in the meta‐analysis were from Europe, North America and Asia. Similarly, in the study by Deadmond et al, there were no significant differences in incidence in patients of different ethnicities while Srour et al, also using the SEER register reported a lower incidence of MPNs among Hispanic Whites and in the Asians/Pacific Islanders . The Swedish Cancer Register does not hold information on race or ethnicity; however, 85–90% of the Swedish population is of Northern European descent and 10–15% of the population are first‐degree immigrants primarily from other European, Middle Eastern and North African countries.…”
Section: Discussionmentioning
confidence: 90%
“…The majority of studies included in the meta‐analysis were from Europe, North America and Asia. Similarly, in the study by Deadmond et al, there were no significant differences in incidence in patients of different ethnicities while Srour et al, also using the SEER register reported a lower incidence of MPNs among Hispanic Whites and in the Asians/Pacific Islanders . The Swedish Cancer Register does not hold information on race or ethnicity; however, 85–90% of the Swedish population is of Northern European descent and 10–15% of the population are first‐degree immigrants primarily from other European, Middle Eastern and North African countries.…”
Section: Discussionmentioning
confidence: 90%
“…Polycythaemia vera is uncommon in females of reproductive age, occurring in less than 0Á3 per 100 000 (Srour et al, 2016). There are only small case series describing the management of pregnancy in patients with PV (Harrison, 2005;Robinson et al, 2005;Griesshammer et al, 2008).…”
Section: Pregnancymentioning
confidence: 99%
“…[2][3][4][5] Median age at diagnosis is 72 years, CMML being rare in young adults. Whole genome sequencing of leukemic cell DNA identified 2 age-related molecular signatures, 6 supporting the idea that aging is the main cause of the disease.…”
Section: Introductionmentioning
confidence: 99%